Protective interaction of human phagocytic APC subsets with Cryptococcus neoformans induces genes associated with metabolism and antigen presentation - Nelson, Benjamin N.; Daugherty, Cheyenne S.; Sharp, Rachel R.; Booth, J. Leland; Patel, Vineet I.; Metcalf, Jordan P.; Jones, Kenneth L.; Wozniak, Karen L. (Frontiers in Immunology, 2022)
Cryptococcal meningitis is the most common cause of meningitis among HIV/AIDS patients in sub-Saharan Africa, and worldwide causes over 223,000 cases leading to more than 181,000 annual deaths. Usually, the fungus gets inhaled into the lungs where the initial interactions occur with pulmonary phagocytes such as dendritic cells and macrophages where the pathogen gets killed or can replicate intracellularly. Previous studies in mice showed that different subsets of these innate immune cells can either be antifungal or permissive for intracellular fungal growth. Our studies tested phagocytic antigen-presenting cell (APC) subsets from the human lung against C. neoformans. Human bronchoalveolar lavage was processed for phagocytic APCs and incubated with C. neoformans for two hours to analyze the initial interactions and fate of the fungus, living or killed. Results showed all subsets (3 macrophage and 3 dendritic cell subsets) interacted with the fungus, and both living and killed morphologies were discernable within the subsets using imaging flow cytometry. Single cell RNA-seq identified several different clusters of cells which more closely related to interactions with C. neoformans and its protective capacity against the pathogen rather than discrete cellular subsets. Differential gene expression analyses identified several changes in the innate immune cell’s transcriptome as it kills the fungus including increases of TNF-α (TNF) and the switch to using fatty acid metabolism by upregulation of the gene FABP4. Also, increases of TNF-α correlated to cryptococcal interactions and uptake. Together, these analyses implicated signaling networks that regulate expression of many different genes – both metabolic and immune - as certain clusters of cells mount a protective response and kill the pathogen. Future studies will examine these genes and networks to understand the exact mechanism(s) these phagocytic APC subsets use to kill C. neoformans in order to develop immunotherapeutic strategies to combat this deadly disease.